Intercomparisons of HIRDLS, COSMIC and SABER for the detection of stratospheric gravity waves - C. J. Wright; M. B. Rivas; J. C. Gille (Atmospheric Measurement Techniques, 2011)
Colocated temperature profiles from the Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC), High Resolution Dynamics Limb Sounder (HIRDLS) and the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) mission are compared over the years 2006–2007 to assess their relative performances for the detection of stratospheric gravity waves. Two methods are used, one based on a simple comparison of the standard deviations and correlation coefficients of high-pass filtered profiles from each instrument, and the other based on Stockwell transform analyses of the profiles for vertical wavelength and temperature perturbation scales. It is concluded, when allowing for their different vertical resolution capabilites, that the three instruments reproduce each other's results for magnitude and vertical scale of perturbations to within their resolution limits in approximately 50 % of cases, but with a positive frequency and temperature bias in the case of COSMIC. This is possibly indicative of a slightly higher vertical resolution being available to the constellation than estimated.